2015
DOI: 10.1056/nejmoa1415447
|View full text |Cite
|
Sign up to set email alerts
|

Trial of Everolimus-Eluting Stents or Bypass Surgery for Coronary Disease

Abstract: Among patients with multivessel coronary artery disease, the rate of major adverse cardiovascular events was higher among those who had undergone PCI with the use of everolimus-eluting stents than among those who had undergone CABG. (Funded by CardioVascular Research Foundation and others; BEST ClinicalTrials.gov number, NCT00997828.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
274
1
18

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 423 publications
(315 citation statements)
references
References 26 publications
22
274
1
18
Order By: Relevance
“…None of the following studies comparing PCI with OPCAB38, 39, 40, 41 were powered for stroke, and none reports the extent of “no‐touch” technique in the CABG group. Conversely, one recent trial assessing midterm outcomes of 438 patients randomly assigned to the PCI with everolimus eluting stents and 442 randomly assigned to the CABG group42 found no difference in the risk of stroke between the 2 groups: hazard ratio 0.86 (0.39–1.93); P =0.72. Interestingly, OPCAB was performed in around two thirds of the cases, and arterial revascularization without manipulation of the aorta was encouraged by the study protocol.…”
Section: Discussionmentioning
confidence: 97%
“…None of the following studies comparing PCI with OPCAB38, 39, 40, 41 were powered for stroke, and none reports the extent of “no‐touch” technique in the CABG group. Conversely, one recent trial assessing midterm outcomes of 438 patients randomly assigned to the PCI with everolimus eluting stents and 442 randomly assigned to the CABG group42 found no difference in the risk of stroke between the 2 groups: hazard ratio 0.86 (0.39–1.93); P =0.72. Interestingly, OPCAB was performed in around two thirds of the cases, and arterial revascularization without manipulation of the aorta was encouraged by the study protocol.…”
Section: Discussionmentioning
confidence: 97%
“…In a randomized trial of patients with multivessel CAD at 27 centers in East Asia, published in 2015, Park et al found that the MACE rate was higher in patients with PCI using everolimus-eluting stents compared with CABG. 27 Also in 2015, an observational registry study of patients with multivessel CAD reported that the risk of death with PCI utilizing everolimus-eluting stents was similar to that observed for CABG. 28 Obviously, the ultimate superior stent is yet to be found.…”
Section: Multiple Coronary Artery Stentsmentioning
confidence: 90%
“…[3][4][5][6] Interventional cardiologists have made rapid additions to their armamentarium for treating complex CAD through the development of newer-generation drugeluting stents (DES) and novel antithrombotic drugs. At the same time, cardiac surgeons have improved revascularization procedures through the implementation of bilateral left internal mammary artery grafts as well as off-pump and minimally invasive surgery.…”
Section: -A Tale Of Two Cities By Charles Dickensmentioning
confidence: 99%